Some Integral Inequalities for Harmonically (α, s)-Convex Functions. (30th July 2019) - Özcan, Serap
Abstract : In the paper, the author introduces a new class of harmonically convex functions, which is called harmonicallyα, s -convex functions and establishes some new integral inequalities of the Hermite-Hadamard type for harmonicallyα, s -convex functions. The properties of the newly introduced class of harmonically convex functions are also investigated. Finally, some applications to special means are given.